Examining the Effect of Cooperative Integrated Reading and Composition (CIRC) on Students’ Reading Comprehension - Napon Wongsuwan; Afiifah Abrora Regiana (Universitas PGRI Semarang, 2023)
The study's overarching goal is to determine whether or not CIRC instruction has a statistically significant effect on students' ability to comprehend narrative literature. In this study, we used a one-group, pre-post-test design for our experiments. Students from SMP Hasanuddin 6 Semarang's eighth grade made up the study's sample population. Twenty-four pupils from VII A were involved as the sample of this study. A reading test was carried out as this study's primary instrument of data collection. Before being taught using the CIRC method, students had a mean score of 40.91, indicating that their reading ability in narrative text was inadequate and needed improvement; after being taught using the CIRC method, students had a mean score of 64.12, indicating that their reading ability in narrative text was good and had already improved. In other words, the CIRC technique works well for teaching students to read narrative texts.